INSIGHTS INTO LINGUISTIC RESEARCH OF PERSPECTIVE IN DRAMA: THE CASE OF O. WILDE’S PLAYS - Tsys, Yu. (Studia Philologica, 2019)
The article focuses on linguostylistic means of representation of perspective in O. Wilde’s plays. The main feature of drama that limits the ways of expression of perspective is absence of the narrator. Thus, in the text of drama perspective can be represented through such narrative elements as prologue, author’s remarks, chorus odes, lines of epic characters and built-in narratives. These narrative elements can implement author’s perspective. The linguostylistic analysis of perspective in O. Wilde comedies lend support to the idea that the main stylistic means of expressing the author’s direct perspective are simile and epithet. The author’s indirect perspective can be interpreted from the lines of characters, it is usually represented in the text by means of irony and sarcasm. Character’s perspective can be interpreted from monologues, dialogues and polylogues and is predominantly verbalised through metaphor and epithet.